Artificial structure selection by economically important reef fishes at North Carolina artificial reefs - Tharp, Ryan M.; Hostetter, Nathan J.; Paxton, Avery B.; Taylor, J. Christopher; Buckel, Jeffrey A. (Frontiers in Marine Science, 2024)
Artificial reefs can play an important role in marine fisheries management by supplementing or enhancing natural habitats. Despite their increased use in recent years, the choice of structures used at artificial reefs remains largely haphazard due to the lack of information on reef structure performance. Few studies have examined the use of different artificial reef structures by individual fish. From 2021-2022, we acoustically tagged 72 black sea bass (Centropristis striata), 34 gag (Mycteroperca mircrolepis), 27 greater amberjack (Seriola dumerili), nine almaco jack (S. rivoliana), and eight red snapper (Lutjanus campechanus) on four artificial reef complexes near Cape Lookout, North Carolina, U.S. Available artificial reef structures consisted of materials of various sizes and heights made of concrete and metal. We tracked tagged fish using a fine-scale positioning system for ~100 days. Black sea bass exhibited high site fidelity to the artificial structure where we caught them, rarely moving away from that structure. The limited movement resulted in low transition probabilities; we conclude that black sea bass do not select for particular artificial structures. Gag and red snapper moved greater distances away from artificial structures and routinely moved between them. Greater amberjack and almaco jack moved the most within the complexes displaying circling behavior around individual structures and were the only species that regularly moved off the artificial reef complexes. Greater amberjack movements away from artificial sites were most commonly directed to surrounding shipwrecks. Whereas gag, red snapper, almaco jack, and greater amberjack used all available structures, they consistently selected for high relief structures, such as vessels, more than other structures. These results will be useful to managers charged with decisions on what types of structures to place at artificial reef complexes to supplement or enhance habitat for economically important fishes.